2015
DOI: 10.1002/bit.25576
|View full text |Cite
|
Sign up to set email alerts
|

Modified amelogenin is a new and versatile nanomaterial for biomedical applications

Abstract: Amelogenin self-assembly is crucial for tooth biomineralization and crystallite enamel orientation. Amelogenin forms stable nanoparticles under physiological conditions. Here, we tested whether the surface properties and binding characteristics of these particles could be modified to enhance amelogenin function as a biomaterial. We evaluated different amelogenin fusion proteins for their ability to form hybrid nanoparticles. As a proof-of-concept, the integrin-binding tripeptide Arg-Gly-Asp (RGD) sequence from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…This makes it possible to produce modified amelogenins in a simple manner, which can be assembled to nanosized aggregates. This has also recently been shown by others . Besides amelogenin fusion proteins, we have also reported that a random mutation amelogenin library can be used to create amelogenins with distinct solubility behavior, further demonstrating the possibilities to engineer the properties of this protein.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…This makes it possible to produce modified amelogenins in a simple manner, which can be assembled to nanosized aggregates. This has also recently been shown by others . Besides amelogenin fusion proteins, we have also reported that a random mutation amelogenin library can be used to create amelogenins with distinct solubility behavior, further demonstrating the possibilities to engineer the properties of this protein.…”
Section: Introductionsupporting
confidence: 78%
“…). Previous studies have shown that different amelogenin variants can be mixed at non‐aggregating conditions and co‐assembled into composite amelogenin aggregates with distinct properties that depend on the proportion of the individual amelogenin variants . In the present study we observed a difference in solubility when rh174CBD and rh174 were mixed (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These findings suggest that TGF-β1 in the secretory-stage enamel binds to the P173, P162, P148 and P103 amelogenins. The full-length amelogenin is a complex molecule consisting of four functional domains: TRAP, Coil, a PXX repeat and a hydrophilic C-terminal domain 35 36 (see Supplementary Fig. S11 ).…”
Section: Discussionmentioning
confidence: 99%
“…DLS analysis has been used to investigate the mechanisms of amelogenin-cell interactions during amelogenesis 36 44 . Porcine secretory-stage enamel contains 50% water, 25% minerals and 25% proteins, although those ratios are different in the outer, outer-inner and inner layers 40 .…”
Section: Discussionmentioning
confidence: 99%